Growth, yield and phytochemical contents of Sabah Snake Grass [Clinacanthus nutans (Burm.f.) Lindau] in relation to plant age, harvesting intervals and potassium applications - Abd Samat, Nur Mardhiati Afifa (2017)
Clinacanthus nutans or Sabah snake grass is a well reputed medicinal herb among locals which therapeutically used to cure various ailments and diseases for its phytochemicals and antioxidants. Various factors including cultural practices may contribute to the changes in growth and phytochemical contents, hence determine the quantity, quality and efficacy of an herb. Current studies focusing on the harvesting (age and intervals) and fertilizer (potassium) were undertaken evaluating growth, yield and phytochemical content of C. nutans. Plants were cultivated through stem cuttings and were harvested at three different age (week 8, week 12 and week 16 after transplanting) and three harvesting intervals (every 8, 12 and 16 weeks, for respective harvesting age) for three consecutive harvests (harvest 1, 2 and 3). After the completion of the first experiment, plants were then treated with five different rates of potassium fertilizer (0, 50, 100, 150, 200 and 250 kg K2O/ha) using muriate of potash (MOP). The experiments were conducted based on Randomized complete block design (RCBD) with appropriate replications. The results show a significant interaction between plant age and harvesting intervals observed in plant height, leaf area, fresh and dry weight of leaves, phenolic content and ferric reducing antioxidant potential activity (FRAP). The highest leaf fresh yield was recorded at the 16-week-old plants (144.13 g) during third harvesting intervals (154.32 g). The leaf to stem ratio, however decreased with plant age while increased with harvesting interval indicating an increment in stem proportion as the plant grow older. The phytochemical contents were also found to be increased with plant age giving the highest total flavonoid content (TFC) and total phenolic content (TPC) accumulated at 16-week-old plant of 7.32 mg GAE/g DW and 10.84 mg quercetin/g DW respectively. The TFC and TPC decreased following the repetitive harvesting with the lowest recorded at first harvesting interval (TFC: 7.13 mg GAE/g DW, TPC: 10.30 mg quercetin/g DW). The antioxidant activities also significantly increased with plant age while decreased in a number of harvesting intervals. Of all identified compounds, shaftoside was found to be the most abundant in C. nutans at any levels of treatments. The order of C-glycosyl flavone compounds detected under different plant age and harvesting intervals based on concentration from high to low were as follows: shaftoside > iso-orientin > orientin > vitexin > iso-vitexin. In second experiment, all plant growth attributes and yield except for the number of branches were increased with increment of potassium rates. Referring to the trend analysis, the growth and development of C. nutans improved gradually with potassium in a positive and quadratic trend from 0 kg K2O/ha to 200 kg K2O/ha before decline slowly at 250 K2O/ha in respective shoot fresh and dry weight, leaf gas exchange, phytochemical contents and antioxidant activities. The optimum rate and the maximum value, however, varied with the parameters. All detected C-glycosyl flavone compounds were highest at 200 kg K2O/ha given shaftoside as the major compound identified. These results obtained in both experiments indicates that the yield and phytochemical quality of C. nutans can be enhanced by regulating the cultural practices. Harvesting at week 12 with one-time interval and applying would be appropriate harvesting method as growth, yield and phytochemicals content of C. nutans were enhanced.An optimum potassium level of 154.75 kg K2O/ha could be the appropriate K application for the cultivation of C. nutans as yield were enhanced and 143 kg K2O/ha of muriate of potash would be the appropriate optimum K rate that would improve the production of phytochemical content in C. nutans.